Pollen sources used by frieseomelitta ihering 1912 (Hymenoptera: Apidae: Meliponini) bees along the course of the rio negro, amazonas, brazil - Abreu, Vanessa Holanda Righetti de; Pimentel, Alyne Daniele Alves; Absy, Maria Lúcia; Rech, André Rodrigo (Acta Botanica Brasilica, 2020)
Insect pollination has influenced the evolution and diversification of angiosperms. Consequently, knowing plants used as food sources by bees, the most important pollinator group, is the first step toward understanding how their ecological relationships works. Pollen source information is also highly relevant for bee management and associated fruit and seed production. Accordingly, to improve understanding of the trophic ecology of these bees and their relationships with native Amazonian plants the current study identified, quantified and compared pollen stored in nests of Frieseomelitta stingless bees along the Rio Negro, Amazonas, Brazil. A total of 31 pollen pots were sampled and found to contain 65 pollen types distributed across 52 genera and 29 botanical families (predominantly Arecaceae, Araliaceae, Fabaceae and Urticaceae). Euterpe was the commonest pollen type, being present in 32.2 % of the analyzed samples. Although the studied bees were generalists, pollen analysis suggested that different Frieseomelitta species may have distinct food preferences. The pollen profile of the studied bees was influenced more by nest location than by species phylogenetic proximity. The current study also provides a list of important plants for native bee management, which could improve beekeeping when grown near managed meliponarine colonies. © 2020, Sociedade Botanica do Brasil. All rights reserved.
Keywords: Amazon; Feeding behavor; Meliponicultura; Stingless bees; Trophic resources